Small corpus studies and ELT : theory and practice - Ghadessy, Mohsen, 1935-; Henry, Alex; Roseberry, Robert L., 1945- (Studies in corpus linguistics, 2001)
Recent developments in this field of small corpus studies, largely brought about by the personal computer, have yielded remarkable insights into the nature and use of real language. This book presents work by a number of leading researchers in the field and covers a series of topics directly related to language teaching and language research. The ultimate aim of this book is to encourage the exploitation of small corpora by the ELT profession to make language learning more effective. In addition to descriptions of the basic corpus analysis tools, chapters in the collection cover syllabus and m.